2018
DOI: 10.1097/01.jaa.0000530288.83376.8e
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum depression in older women

Abstract: Postpartum depression, which affects 10% to 20% of women in the United States, can significantly harm the health and quality of life for mother, child, and family. This article reviews the risk factors, pathophysiology, clinical manifestations, diagnosis, and treatment of postpartum depression with specific focus on women of advanced maternal age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…The relationship between age and perinatal depressive symptoms is not well established in the literature [8]. Our results are consistent with studies suggesting that older women are at higher risk of pregnancy depressive symptoms [40]. However, the strength of the cross-sectional associations found in the present investigation was weak, so the results should be interpreted with caution and replication should be encouraged.…”
Section: Factors Cross-sectionally Associated With Prenatal Depressivsupporting
confidence: 81%
“…The relationship between age and perinatal depressive symptoms is not well established in the literature [8]. Our results are consistent with studies suggesting that older women are at higher risk of pregnancy depressive symptoms [40]. However, the strength of the cross-sectional associations found in the present investigation was weak, so the results should be interpreted with caution and replication should be encouraged.…”
Section: Factors Cross-sectionally Associated With Prenatal Depressivsupporting
confidence: 81%
“…As mothers within an age range of 26-30 years and with the occupation of spauses (employee) and type of pregnancy (wanted) had the lowest rate of depression. Strelow in the United States, on the other hand, has shown that younger mothers, aged 15-24 years (compared to older mothers of 25-29 years), are less prone to depression [37]. Guin [38] also stated that mothers within an age range of 36-40 years reported the highest rate of depression, and those within a range of 20-25 years had the lowest.…”
Section: Discussionmentioning
confidence: 99%
“…The stress conditions of pregnant women especially primigravidas can occur and continue until postpartum. Strewlow et al (2018) reported that primigravida mothers have a 50-80% risk of postpartum depression. Antenatal care plays an important role in the safety of the mother and fetus, minimizes pregnancy risks, and reduces postpartum mortality.…”
Section: Cortisolmentioning
confidence: 99%